Seismic Performance and Construction Stability of Long- Span Continuous Rigid-Frame Bridges with Tall Piers - Yadav, Raghabendra; Shrestha, Bharat Lal; Paikara, Ramesh Kumar; Gupta, Dinesh Kumar; Yadav, Preshna (KTFT Journal, 2024)
This study investigates the construction stability and seismic performance of long-span continuous rigid-frame bridges (CRFBs) with extremely tall piers, a first for Nepal, exemplified by Bridge 37 on the Kathmandu – Terai/Madhesh Fast Track (Expressway) Road Project (KTFT). CRFBs, constructed using the Free Cantilever Method, offer advantages such as smooth driving, low cost, adaptability, and aesthetics. However, their design and construction in mountainous regions require meticulous detailing, particularly to handle the flexural requirements and seismic loads. Using finite element modelling with Midas Civil, this study evaluates construction loads, wind loads, and incidental loads. Key analyses include interaction curves, modal analysis, response spectrum analysis, and construction stage analysis. Results indicate that the fundamental time period of the bridge is 2.847 seconds with a fundamental frequency of 0.35 Hz. Maximum displacements due to seismic loading were found to be 220mm and 357 mm in x and y directions, respectively. The findings align with contemporary research, demonstrating adequate stability and performance under seismic conditions. This research provides valuable insights and guidelines for the design and construction of CRFBs in seismic regions, contributing to enhanced safety, stability, and durability of bridge infrastructure in Nepal.